Potential of native forests for the mitigation of greenhouse gases in Salta, Argentina - Manrique, Silvina Magdalena (2011)
Carbon stocks were assessed in three archetypal forest ecosystems in the province of Salta, Argentina, namely Yungas, Chaco, and shrublands located around Chaco. Over a total area of about 7000 m2 , detailed measurements of woody biomass were conducted using structural information such as diameter at breast height (dbh), total height, and stem height. At the same time, the wet weight of herbaceous, shrubs, and litter was registered within that area. Soil samples were also collected to determine parameters such as bulk density and organic carbon. The above-ground tree biomass (AGB) was quantified by two non-destructive methods. This biomass was expressed from each reservoir studied in t.ha 1 and the carbon content was then calculated using a factor of 0.5. Carbon stocks in the ecosystems studied were 162, 92, and 48 tC.ha 1 for Yungas, Chaco, and shrublands, respectively. Our results show that carbon is concentrated in the soil or as AGB. The latter is the most important reservoir in Yungas, while the soil plays this role in the other two, drier environments. In the province of Salta, native forests play a significant role in the mitigation of greenhouse gases. Our results reveal the magnitude of carbon stocks in some characteristic regional native forests, and estimate their carbon sequestration potential. These results could be useful to inform policy makers in charge of negotiations related to conservation and sustainable management of native forests, and be a relevant input for the formulation of more comprehensive land use planning processes in the region.